Bekerjanya Politisasi Identitas pada Pilkada Sumut 2018: Menakar Pengaruh Isu Agama Terhadap Kemenangan Edy Rahmayadi dan Musa Rajekshah - Irfan Prayogi; Ian Pasaribu (Badan Pengawas Pemilihan Umum, 2018)
This article will describe what is the winning factor for Edy Rahmayadi and Musa Rajekshah in the 2018 Sumatera Utara contestation of regional elections. The author sees Political Identity greatly influencing the course of democracy in North Sumatra due to differences in religious identity between the two pairs of contesting candidates. The politics of identity centered on the politicization of shared identity is an important base of glue in group collectivity. Identity is then politicized through extreme interpretation to gain support from the majority of the community both in race, ethnicity and religion. This research is a qualitative research with descriptive analysis. The data collection techniques through interviews as primary data and secondary data in the form of news, journals, books, and documents related to the results of Sumatera Utara 2018 regional elections. Findings from this study, the author saw Edy-Musa utilizing Islamic discourse as a power to obtain votes from Islamic circles. This is evident from the post-election vote acquisition in certain regional bases, as well as the social conditions of the community before the vote. In addition, Islamic discourse is clearly present through banners calling for choosing Muslim leaders, morning prayer in congregation and other identity issues as an effort to influence people’s preferences to make choices on voting. This paper seeks to understand identity politics as a form of popular strategy and the implications that arise in the electoral politics.